ANATOMI DAN IDENTIFIKASI 17 JENIS KAYU KURANG DI KENAL Anatomy and identification of 17 lesser known wood species - Y I Mandang (Jurnal Penelitian Hasil Hutan, 1990)
~   ..  anil anotOmical• ffOtura   of   17 luaer   #mown  wood  apeciea (1 ta•ilaa)      ,,,.,..dwldikd   and  compared.   There•arec :fhrff'  of   tlaem uilaich  haw  deebrative   appearance.   Le. Wrip~ia• tomentoa.   fenumdoa.•  ~eloba     and-"1tophtorum~,.,_.:,                                      •,'•.•                                                                  .,          ..                                                ,_                ..          •.For  identificatio11  p~.;            ...veral   important  features  were noted.  Tlaei_o~cur at leGlt •;n {!ne _member   of  the folow inl .tazo_n _;   lJ. ~,,.;- rfnl   {K>reo..f!.#1  W,Ood in  Bipao~ae;       2J scalilrlform   perfo1'ltion  plate  in Ala111iaceae; 8) veatured pit  in CaualpiniDc~e;     4}.  luJmoceilular    ray. in  Aceraceae,  Bignoniaceae  and  Cae10ltJjnl4e«le;. SJ  ray atoned in  Cae1alpiniaceae;6) iilica• badlei;1n''Dlalium    arid SWbltonia;  7) vertical  chains of cry1tals  in•Ca.,,inloaeO'e;,8)     :ae.ptote fibe,.,  in•AnacardiaMi~' B~               arid Caesalplnlaceae;   9)  radial  mtercellular  canal in  Anacardiaceae  and Buneraceae.